Safety and Efficacy of Jenacid® Herbal Product Against Indomethacin-Induced Ulcers in Albino Wistar Rats - Kiprotich, Joshua; Timothy, Neeza; Mwandah, Daniel C.; Yadesa, Tadele M. (Cureus, 2024)
Background: Jenacid Herbal Product (JHP) used for treating peptic ulcer disease in Uganda, sold over the counter, is approved by the National Drug Authority as a Traditional Herbal Product number THP 482. There have been no published studies on its safety and efficacy. Objective: This study aimed to assess potential acute and subacute toxicity as well as the efficacy of JHP. Method: An acute toxicity test was performed on Swiss Albino Wistar rats using Lorke’s method at single oral doses of 10-5000 mg/kg. General change in behavior, adverse effects, and mortality were determined. In the subacute study, Wistar rats received daily oral doses of 250, 500, and 1000 mg/kg of JHP for 28 days. Body weight and biochemical and hematological parameters were measured at the end of the experiment. For the efficacy study, rats were randomly grouped into six groups (n=5). Gastric ulceration induced with a single oral dose of indomethacin 25 mg/kg. One group was humanely sacrificed under halothane anesthesia to confirm ulceration. Treatments included distilled water (negative control), 20 mg/kg omeprazole (positive control), 250, 500, and 1000 mg/kg of JHP for seven days, after which animals were sacrificed, stomachs excised out, observed for gastric lesions (number and severity), and scored. Results: The acute toxicity study showed oral LD50 of JHP was above 5000 mg/kg. A subacute toxicity study of JHP had no observable toxicity symptoms or significant variation in body weight, food and water consumption, hematological parameters, or mortality. Elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were noted at 1000 mg/kg but within normal ranges. A significant decrease in total protein was observed at 500 mg/kg and 1000 mg/kg. JHP demonstrated ulcer-healing properties, with the highest efficacy at 500 mg/kg. Conclusion: JHP is effective against ulcers with no significant adverse effects. However, chronic use of very high doses may cause a reduction in total protein levels.
Keywords: Acute toxicity; Jenacid herbal product; Peptic ulcer disease; Phytochemical composition; Subacute toxicity